Telecommuting as a True Workplace Alternative - Kelli A. Green; Mayra López; Allen Wysocki; Karl Kepner (EDIS)
This document includes a detailed description and definition of telecommuting, lists the desirable traits of telemanagers and teleworkers, and discusses the benefits and challenges of telecommuting. This is EDIS document HR 021, a publication of the Department of Food and Resource Economics, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida, Gainesville, FL. Published April 2003.